Jamaica's farmers get new information centre - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Farmers get new information centre , Jamaica Gleaner, February 2001 A new information centre for farmers has been set up to provide support services for members of the Manchester and St Elizabeth Vegetable Growers´ Association.